The Application of Deep Breathing Relaxation on Pain Scale Reduction in Postpartum Patients in the Mawar Maternity Ward of Kardinah Regional General Hospital, Tegal City - Intan Wulandari, Sinta; Wahyuni Romadhon, Lily (INDOGENIUS, 2025)
Background & Objective: A cesarean section is performed when spontaneous or vaginal delivery is not possible due to risks to either the mother or the baby. Pain during childbirth with cesarean section can be minimized using two methods: pharmacological and non-pharmacological. One intervention that can be provided is deep breathing relaxation technique, which helps induce a relaxed state by controlling breathing, thereby reducing pain during childbirth and aiding recovery. Method: This study is descriptive, using a case study method, with deep breathing relaxation performed 15 times, divided into 3 cycles. In each cycle, the patient was asked to take 5 deep breaths with one rest period. The criteria for inclusion were patients who had undergone a cesarean section with postpartum hemorrhage (PPH) as an indication, patients with pain complaints, and those who signed an informed consent form. Result: The results of this study showed that after three days of deep breathing relaxation intervention, patients reported feeling more relaxed, with their pain diverted and reduced. There was a decrease in pain scale from 6 to 2, with the assistance of dexketoprofen medication. Conclusion: Deep breathing relaxation can be an effective management strategy for reducing pain scale with medication assistance.